Synergistic highly potent targeted drug combinations in different pheochromocytoma models including human tumor cultures - Fankhauser, Maria; Gieldon, Laura (Endocrinology, 2019)
There are no officially approved therapies for metastatic pheochromocytomas apart from ultratrace 131I-metaiodbenzylguanidine therapy, which is approved only in the United States. We have, therefore, investigated the antitumor potential of molecular-targeted approaches in murine pheochromocytoma cell lines [monocyte chemoattractant protein (MPC)/monocyte chemoattractant protein/3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)], immortalized mouse chromaffin Sdhb−/− cells, three-dimensional pheochromocytoma tumor models (MPC/MTT spheroids), and human pheochromocytoma primary cultures. We identified the specific phosphatidylinositol-3-kinase α inhibitor BYL719 and the mammalian target of rapamycin inhibitor everolimus as the most effective combination in all models. Single treatment with clinically relevant doses of BYL719 and everolimus significantly decreased MPC/MTT and Sdhb−/− cell viability. A targeted combination of both inhibitors synergistically reduced MPC and Sdhb−/− cell viability and showed an additive effect on MTT cells. In MPC/MTT spheroids, treatment with clinically relevant doses of BYL719 alone or in combination with everolimus was highly effective, leading to a significant shrinkage or even a complete collapse of the spheroids. We confirmed the synergism of clinically relevant doses of BYL719 plus everolimus in human pheochromocytoma primary cultures of individual patient tumors with BYL719 attenuating everolimus-induced AKT activation. We have thus established a method to assess molecular-targeted therapies in human pheochromocytoma cultures and identified a highly effective combination therapy. Our data pave the way to customized combination therapy to target individual patient tumors.